Relationship between anxiety and fatigue in dementia family caregivers: hope as a mediator - Jiin-Ling Jiang; Shing-Ling Chang; Ke-chieh Wang; Yu-Chin Ma (BMC Nursing)
Abstract Background This study investigated the mediating role of hope in the relationship between anxiety and fatigue in family caregivers of individuals with dementia. Methods A cross-sectional design was employed, with data collected from 84 family members caring for a patient with dementia in Tzu Chi Hospital in eastern Taiwan. Instruments were the Herth Hope Index, fatigue, and anxiety scales. Results The findings revealed a significant negative correlation between fatigue and hope (r = −.431, p <.01), a significant positive correlation between fatigue and anxiety (r =.584, p <.01), and a significant negative correlation between hope and anxiety (r = −.364, p <.01). Furthermore, the results indicated that anxiety indirectly predicted fatigue through hope. Hope was a mediating variable between anxiety and fatigue, accounting for 15.6% of the mediating effect. Conclusions Prioritizing the physical and mental health of family caregivers of individuals with dementia by fostering hope can help alleviate their caregiving fatigue and enhance their overall well-being.